Management in Creating a Learning Environment that Enhances Elementary Students’ Intrinsic Motivation - Agusalim; Saleh, Rachman; Riniati, Wa Ode (TAKSONOMI: Jurnal Penelitian Pendidikan Dasar, 2025)
A positive and adaptive learning environment plays a crucial role in enhancing the intrinsic motivation of elementary school students. As the primary managers of the classroom, teachers hold a strategic position in creating learning conditions that support students’ emotional, social, and academic needs. This study aims to examine teacher management in fostering a learning environment that promotes students’ intrinsic motivation through five key aspects: structured lesson planning, the creation of a positive classroom atmosphere, the provision of exploratory freedom, the empowerment of student roles, and the adjustment to individual needs. The research employed a descriptive qualitative method through semi-structured interviews with five elementary school teachers from various grade levels. The findings indicate that teachers have implemented student-centered learning approaches through flexible and responsive strategies. Teachers design lesson plans based on students’ needs, create a safe and enjoyable classroom climate, and provide space for students to express themselves and take active roles. Challenges faced include limited time, large class sizes, and diverse student characteristics. Nevertheless, teachers strive to establish a supportive learning environment that motivates students to engage in independent and meaningful learning. This study highlights the importance of adaptive teacher management in enhancing intrinsic motivation among elementary school students.